The effect of spiritual counseling based on the sound heart model on resilience and parenting competence in mothers with intellectually disabled children - Arefeh Sadeghi; Anahita Khodabakhshi-Koolaee; Minoo Asadzandi (Preventive Care in Nursing and Midwifery Journal)
Background: Having a child with mental ability is very challenging for the mother as the main caregiver. Objectives: The present study aimed to examine the effectiveness of spiritual counseling based on the sound heart model (SHM) on the resilience and parenting competence of mothers with intellectually disabled children. Methods: This experimental study was conducted using a pre-test and post-test design with a control group. The research population consisted of all mothers with intellectually disabled children studying at Shahid Atqaei Educational Complex in Tehran in 2023. A total of 40 mothers were selected as the participants through voluntary sampling and were randomly placed into two control and experimental groups. SHM sessions were conducted in ten 90-minute sessions weekly for the mothers in the experimental group. Connor-Davidson Resilience Scale (CD-RISC) and Parenting Sense of Competence Scale (PSOC) were used to collect data. Data were analyzed using univariate analysis of covariance (ANCOVA) and independent samples t-test in SPSS-24 software. Results: The mean (SD) resilience score increased significantly from 65.06 (5.63) before the SHM intervention to 74.40 (10.11) after the SHM intervention (p<0.021). However, a comparison of the mean (SD) parental competence score before and after SHM intervention did not show a statistically significant difference [56.60 (10.11) vs. 68.80 (9.19); p<0.091]. Conclusion: The SHM intervention helped mothers with mentally disabled children to create a strong bond with the eternal power of God. The intervention also improved the mothers’ resilience and helped them accept the reality of life. This treatment can be used in mother and child care programs.